Relationship Between Concentration and Volleyball Passing Skills Students at State Junior High School 1 Patuk - Russetya, Rama Andietio; Ngatman; Astuti, Triyani (Indonesian Journal of Sport Management, 2024)
One factor that is thought to have a strong influence on passing quality is the level of concentration. Good concentration allows students to anticipate the direction of the ball, adjust their body position, and optimize their reaction time. Conversely, poor concentration can lead to attention lapses, errors in decision-making, and delayed reactions to game stimuli. This study aims to determine the relationship between concentration and passing skills in volleyball among extracurricular participants at Junior High School Negeri 1 Patuk. This research is quantitative with a correlational approach. The population in this study is 24 junior high school students participating in the volleyball extracurricular activity at State Junior High School 1 Patuk, consisting of 12 boys and 12 girls, selected using total sampling technique. The concentration instrument used was the Grid Concentration Test, and passing skills were measured using a test instrument from the Ministry of Education and Culture. The data analysis technique used was correlation Product Moment analysis. The results of the study indicate that there is a significant relationship between concentration and passing skills in volleyball among extracurricular participants at State Junior High School 1 Patuk, with a calculated r value of 0.628 > table r value of 0.396 and a p-value of 0.000 < 0.05. The contribution of concentration to the passing skills of volleyball players in the extracurricular program at State Junior High School 1 Patuk is 39.40%. : Based on the results of data analysis, description, testing of research results, and discussion, it can be concluded that there is a significant relationship between concentration on volleyball passing skills of extracurricular participants at State Junior High School 1 Patuk, with a calculated r value of 0.628 and a contribution of 39.40%.